2018
DOI: 10.1186/s13287-018-0781-9
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic mesenchymal stem cells improve ovarian function in natural aging through secreting hepatocyte growth factor and epidermal growth factor

Abstract: BackgroundAlthough many reports show that various kinds of stem cells have the ability to recover function in premature ovarian aging, few studies have looked at stem cell treatment of natural ovarian aging (NOA). We designed this experimental study to investigate whether human amniotic mesenchymal stem cells (hAMSCs) retain the ability to restore ovarian function, and how hAMSCs work in this process.MethodsTo build the NOA mouse model, the mice were fed for 12–14 months normally with young fertile female mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 28 publications
1
82
0
3
Order By: Relevance
“…In support of our findings, recent studies have suggested the paracrine mechanism of mesenchymal stem cell therapy [44]. Our previous study also demonstrated that hepatocyte growth factor (HGF) and epidermal growth factor (EGF) secreted from hAMSCs play a critical role in reversing ovarian aging [17]. In this study, VC-hAECs secreted more trophic factors than hAECs, including HGF and EGF (Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In support of our findings, recent studies have suggested the paracrine mechanism of mesenchymal stem cell therapy [44]. Our previous study also demonstrated that hepatocyte growth factor (HGF) and epidermal growth factor (EGF) secreted from hAMSCs play a critical role in reversing ovarian aging [17]. In this study, VC-hAECs secreted more trophic factors than hAECs, including HGF and EGF (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…To date, various kinds of stem cells have been investigated to treat POI, including adipose-derived mesenchymal stem cells (hADSCs) [6], fetal liver mesenchymal stem cells [9], bone marrow mesenchymal stem cells (hBMSCs) 2 [10], human umbilical cordderived mesenchymal stem cells (hUCMSCs) [11,12], human amniotic epithelial cells (hAECs) [13,14], human amniotic fluid stem cells [15], and human amniotic mesenchymal stem cells (hAMSCs) [16,17]. Previous studies have indicated that human amnionderived stem cells are easier, less invasive, and more cost-effective than to obtain hADSCs and hBMSCs because amniotic tissues are discarded after delivery [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…Inactivating it in mice by EGFR-specific inhibitors or knockdown of EGFR in osteoprogenitors and osteoblastic cells results in bone loss because of a decreased number of bone marrow mesenchymal progenitors (18). Recently, it was reported that EGFR signaling protected cells from senescence and inhibited tissue aging (19)(20)(21), and blocking EGFR signaling promoted cell senescence and tissue aging (21). These studies strongly suggest that the EGFR signaling in osteoprogenitors might be important in prevention of cell senescence and regulation of cortical bone metabolism.…”
mentioning
confidence: 99%
“…Current studies have indicated that, in the normal developmental period of the ovarian follicular cycle, all phases of follicular atresia are closely related to the activity levels of granulosa cells (Sun et al, 2012). Moreover, apoptosis in granulosa cells is the principal mechanism driving follicular atresia and arrest (Ding et al, 2018b). It has been speculated that abnormal folliculogenesis is probably due to increased apoptosis and decreased proliferation of granulosa cells (Ding et al, 2018c).…”
Section: Introductionmentioning
confidence: 99%